STRATEGI PERENCANAAN DAN PERANCANGAN REDESAIN BALAI LATIHAN KERJA KOTA SURAKARTA - Bernadeta Fidela Putri; Hari Yuliarso; Ummul Mustaqimah (Universitas Sebelas Maret Surakarta, 2017)
Abstract: The working world demands to the skilled workers encourage the job seekers attending non-formal training and education to increase their skills and expertise. In this case the Ministry of Manpower and Transmigration through the Technical Managing Unit (UPT) Vocational Training Center (BLK) have important role in preparing the job training. Surakarta Vocational Training Center (BLK) is one of the training center located in Surakarta city which serves as a training and education place for the job seekers in their productive age from the city. As a potential educational and training facilities that still work properly, this building still has problems in some aspects, therefore in an attempt to keep its function well, need a plan to redesign. The redesign will be consists of creating a space to cater all the activitiesin Surakarta Vocational Training Center and taking form fitting to introduce its existence to society. The redesign method is Post Occupancy Evaluation (POE) on the conditions and elements of the existing buiding, with the redesign strategy that emphasizes functional aspects, technical aspect such as building physical condition, and behavioural aspects to be solved in accordance with the concept of redesigning. This redesign method will be a reference in consideration of planning and design for the new building. The redesign of Vocational Training Center (BLK) in Surakarta city aims to improve the condition of the building and its surroundings in order to provide convenient education and training center. Keywords: Post Occupancy Evaluation (POE), Redesign, Surakarta City, Vocational Training Center.